(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Immersive language learning refers to an approach where learners are fully surrounded by the target language, often through direct interaction in environments where the language is spoken. This method mimics natural language acquisition, similar to how children learn their first language. The benefits of immersive learning are vast, as it enhances comprehension, improves speaking fluency, and increases cultural understanding. Immersion helps learners to practice the language in context, facilitating quicker and more effective learning. It also allows learners to experience authentic, real-world language use, which enhances vocabulary retention and helps them develop practical communication skills.